1968
DOI: 10.1002/ar.1091620109
|View full text |Cite
|
Sign up to set email alerts
|

The origin and survival of gastric parietal cells in the mouse

Abstract: Using microradioautography, the origin of the gastric parietal (and zymogen) cells was deduced by observing the time of appearance of labelled parietal cells in relation to the other labelled cells i n the gastric mucosa. In order to see whether the parietal cell divides in the adult mouse, time grain count curves of the labelled parietal cells were made from animals which were killed at 1-291 days after thymidine SH injection DPT). Parietal cell survival was followed by observing the disappearance of the labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

1973
1973
1997
1997

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(21 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…Some authors described the occasional but temporary presence of labeled parietal cells after injection of 3H-thymldlne (CHEN and WITHERS, 1975;TAMURA and FUJITA, 1983), while others failed t0 see it (RAGINS et al, 1968;KATAOKA, 1970;WILLEMS et al, 1972;YEOMANS et al, 1976). In the present study, labeled immature parietal cells were rarely found in the adult mouse 1 hr after the injection of 3H-thymidine.…”
Section: Discussionsupporting
confidence: 40%
“…Some authors described the occasional but temporary presence of labeled parietal cells after injection of 3H-thymldlne (CHEN and WITHERS, 1975;TAMURA and FUJITA, 1983), while others failed t0 see it (RAGINS et al, 1968;KATAOKA, 1970;WILLEMS et al, 1972;YEOMANS et al, 1976). In the present study, labeled immature parietal cells were rarely found in the adult mouse 1 hr after the injection of 3H-thymidine.…”
Section: Discussionsupporting
confidence: 40%
“…The latter cells are known to differentiate into surface mucous cells as well as into parietal cells [33], The fact that proliferating ECL cells were observed predominantly in the lower parts of the oxyntic mucosa suggests that ECL cells proliferate independently from the progenitor cells. However, labeling of immature ECL cells or ECL cell progeni tors might be difficult to detect.…”
Section: Discussionmentioning
confidence: 99%
“…However, many reports have dealt with the absence of mitotic activity in the parietal cells (HUNT, 1957;HUNT and HUNT, 1962;LIPKIN et al, 1963;RAGINS et al, 1968;LAWSON, 1970;WATTEL and GEUZE, 1977) except for a few (CHEN and WITHERS, 1975). There are also some papers emphasizing that the parietal cells are transformed from other kinds of cells such as surface mucous cells (CORPRON,1966;WINBORN et al, 1974) or mucous neck cells (RAGINS et al, 1968). Detailed observations using electron microscopic autoradiograp y of 3H-TdR are necessary to solve these problems.…”
Section: Discussionmentioning
confidence: 99%